Study of Nutritional Risk Assessment and Clinical Outcome in Critically ill Covid-19 Patients at a Tertiary Care Institute in North India - Mishra, Ajay (Current Overview on Disease and Health Vol. 7, 2023)
Background: Malnourished patients in an intensive care unit have a poorer prognosis and survival. The use of nutritional clinical scores may assist in the detection of malnutrition in hospitalized patients. Nutritional clinical scores are more accurate than using a single nutritional parameter. Aim: To assess the nutritional risk and to evaluate the association between nutritional risk and in-hospital mortality in patients with severe Covid-19 infection. Methods: In this retrospective study, 119 severe Covid-19 patients admitted to the Intensive Care Unit and High Dependency Unit were included. A modified NUTRIC score was used to assess the nutritional risk for each patient. A score of \(\ge\)5 was used to categorize the patient to have a high nutritional risk. Data with normal distribution requirements were represented as mean ± SD. The results of comparing the correlation between two continuous variables were indicated by the correlation coefficient (r) using correlation analysis. The Association of nutritional risk with ICU 28-day mortality risk was assessed using univariate Cox proportional hazards regression analysis. A result was deemed statistically significant when p <0.05. Results: The study population was predominately elderly, with a median age of 70 years (IQR 67-76). Overall, the higher nutritional risk was observed in 16(13%) patients and a low nutritional risk was observed in 103(87%) patients. A strong association was observed between increasing mNUTRIC score and mortality (\(χ\)2=65.32; p<0.001). The ability of the mNUTRIC score for predicting mortality was 0.952 (95%CI 0.9-1.0, p<0.001). Univariate Cox proportional hazards regression analysis showed higher mortality risk in patients with high nutritional risk (HR=2.25, 95% CI:1.51-3.36, p<0.001). Conclusion: Pre-hospital nutritional status represents an important prognostic factor in patients hospitalized for COVID-19. The modified NUTRIC score, a validated nutritional assessment tool for critically ill patients, is useful to determine nutritional risk in severe COVID-19 patients for a better outcome.